2022
DOI: 10.21608/zjfm.2022.101126.1093
|View full text |Cite
|
Sign up to set email alerts
|

Lactate and S100 protein as early biochemical indicators of birth neonatal asphyxia caused by intrauterine umbilical cord strangulation: a medicolegal view

Abstract: Background: From a forensic pathologist's perspective, there are several aspects of the perinatal postmortem that are particularly important if the baby was born alive or dead. In cases of litigation for perinatal morbidities occurring in hospitals, access to the obstetric and neonatal notes if the baby is born alive and dies a few hours or days later is essential to reach a correct interpretation and conclusion. Hypoxic ischemic encephalopathy (HIE) after prenatal asphyxia is an important cause of neonatal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In the present study, a statistically significant increase was found in the S100B concentration of calves with perinatal asphyxia compared to healthy calves at the time of admission, 24, 48, and 72 h. Higher S100B concentrations in calves with perinatal asphyxia compared to healthy calves have been associated with the development of hypoxic-ischemic encephalopathy [ 50 , 51 ]. In our study, the concomitant elevation of S100B, lactate [ 52 , 53 ], and UCHL1 concentrations in calves with perinatal asphyxia supports the development of hypoxic-ischemic encephalopathy.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In the present study, a statistically significant increase was found in the S100B concentration of calves with perinatal asphyxia compared to healthy calves at the time of admission, 24, 48, and 72 h. Higher S100B concentrations in calves with perinatal asphyxia compared to healthy calves have been associated with the development of hypoxic-ischemic encephalopathy [ 50 , 51 ]. In our study, the concomitant elevation of S100B, lactate [ 52 , 53 ], and UCHL1 concentrations in calves with perinatal asphyxia supports the development of hypoxic-ischemic encephalopathy.…”
Section: Discussionsupporting
confidence: 62%
“…In term and preterm infants with hypoxic-ischemic encephalopathy, S100B concentration was found to be elevated within the first 72 h [ 50 ]. In contrast, Nagdyman et al [ 51 ] reported that S100B is rapidly released in hypoxic brain injury and returns to normal ranges within 48 h. Previous studies showed that in the umbilical cord blood of infants born with neonatal asphyxia S100B and lactate concentrations were increased, and these markers could be helpful as an early predictive marker for diagnosis of neonatal hypoxic-ischemic encephalopathy [ 52 , 53 ]. In the present study, a statistically significant increase was found in the S100B concentration of calves with perinatal asphyxia compared to healthy calves at the time of admission, 24, 48, and 72 h. Higher S100B concentrations in calves with perinatal asphyxia compared to healthy calves have been associated with the development of hypoxic-ischemic encephalopathy [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%